Effects of Land Use on the Ecohydrology of River Basin in Accordance with Climate Change - Halecki, Wiktor; Bedla, Dawid; Ryczek, Marek; Radecki-Pawlik, Artur (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Water deficit affects various regions of the world. Effective approach can be based on ecohydrological solutions and the design of blue-green infrastructure. In our scientific book, we focused on papers that consider water management and adaptation of urban and rural development areas to the progressive climate change. The Special Issue includes a drought-prone place (valleys in Mexico City), reflections on the state and water resources in Lithuania, and engineering and technical articles from China and Poland. In addition, one chapter is dedicated to grassland protection in mountainous areas.